Alguns fatores associados a excesso de peso, baixa estatura e déficit de peso em menores de 5 anos Some risk factors associated with overweight, stunting and wasting among children under 5 years old - Márcia R. Vitolo; Cíntia M. Gama; Gisele A. Bortolini; Paula D. B. Campagnolo; Maria de Lourdes Drachler (Elsevier, 2008)
OBJETIVO: Examinar fatores socioeconômicos e outras condições de vida familiar associadas a excesso de peso, baixa estatura e baixo peso para a estatura em menores de 5 anos. MÉTODOS: Estudo transversal avaliou 3.957 crianças entre 1 mês e 5 anos de idade durante campanha nacional de imunização no município de São Leopoldo (RS) em 2002. As condições socioeconômicas e de saneamento das áreas de abrangência das unidades de saúde foram agrupadas por análise de cluster dos setores do censo populacional de 2001. RESULTADOS: Déficit de peso para estatura ocorreu em 2,6% das crianças, baixa estatura em 9,1% e excesso de peso em 9,8%. A regressão logística multivariada sugere que os fatores associados à chance de excesso de peso foram: área de condições socioeconômicas alta (RC = 1,47; IC95% 1,09-1,96), filhos únicos (RC = 1,44; IC95% 1,00-2,07) e peso ao nascer ≥ 2.500 g (RC = 2,21; IC95%1,27-3,83). A chance de déficit de peso associou-se ao baixo peso ao nascer (RC = 3,46; IC95% 2,06-5,80) e idade da mãe < 20 anos (RC = 1,99; IC95% 1,09-3,62). A baixa estatura associou-se à área de condições socioeconômicas baixas (RC = 2,36; IC95% 1,51-3,69), três ou mais irmãos (RC = 3,12; IC95% 2,18-4,47), peso ao nascer < 2.500 g (RC = 3,49; IC95% 2,53-4,80), idade < 36 meses (RC = 1,77; IC95% 1,37-2,29) e idade materna < 20 anos (RC = 1,60; IC95%1,09-2,35). CONCLUSÕES: Excesso de peso e baixa estatura foram os principais desvios antropométricos observados neste estudo, constituindo prioridades que devem ser consideradas nas políticas públicas atuais. OBJECTIVE: To explore whether socioeconomic and sanitary conditions, maternal and child factors are associated with overweight, stunting, and wasting in children under five year old in the city of São Leopoldo, southern Brazil. METHODS: Cross-sectional study of 3,957 children aged 1 month to 5 years conducted in all primary care services of the city during the National Children's Vaccination Day in 2002. Maternal and child factors were assessed by a questionnaire. Children's height and weight were measured. Cluster analysis was used to group the areas served by the primary care services according to socioeconomic and sanitary conditions of the census tracts assessed by the 2001 National Census. RESULTS: Wasting was observed in 2.6% of children, stunting in 9.1% and overweight in 9.8%. The multivariable logistic regression model suggests that overweight was associated with higher socioeconomic status and better sanitation of the area (OR = 1.47; 95%CI 1.09-1.96), single child (OR = 1.44; 95%CI 1.00-2.07) and birth weight ≥ 2,500 g (OR = 2.21; 95%CI 1.27-3.83). Wasting was associated with low birth weight (OR = 3.46; 95%CI 2.06-5.80) and mother's age < 20 years (OR = 1.99; 95%CI 1.09-3.62). Stunting was associated with low socioeconomic status and poor sanitation of the area (OR = 2.36; 95%CI 1.51-3.69), three or more siblings (OR = 3.12; 95%CI 2.18-4.47), low birth weight < 2,500 g (OR = 3.49; 95%CI 2.53-4.80), child age < 36 months (OR = 1.77; 95%CI 1.37-2.29) and mother's age < 20 years (OR = 1.60; 95%CI 1.09-2.35). CONCLUSIONS: Overweight and stunting were the major anthropometric problems and therefore should be a priority for public policies.